The Effect of Education Through Aniamted Videos and Booklets on Parents’ Knowledge Regarding Social Development Stimulation in Preschool-Aged Children - Maylika Nisa Alfian; Ferika Indarwati; Rahmah Rahmah; Istinengtyas Tirta Suminar (Malahayati Nursing Journal, 2026)
ABSTRACT Developmental disorders among Indonesian children remain high, with 27.5% experiencing delays and 9.5–14.2% of preschoolers having socio-emotional problems. Limited stimulation and improper gadget use during the critical 0–6-year period increase the risk, making parental education and SDIDTK important for early detection and stimulation. This study evaluated the effectiveness of animated video and booklet education in improving parents’ knowledge of social development stimulation. Using a quasi-experimental design with 120 parents, knowledge was measured through pretest–posttest and analyzed with descriptive statistics, normality tests, Wilcoxon, and Mann–Whitney tests. Respondent characteristics were homogeneous (p 0.05). The Wilcoxon (p = 0.761) and Mann–Whitney results (pretest p = 0.974; posttest p = 0.183) showed no significant differences. Although knowledge increased slightly, the media were not effective, indicating the need for more interactive and engaging educational materials. Keywords: Parental Knowledge, Social Development Stimulation in Children, Videos and Booklet.